Efficacy of dexmedetomidine in prevention of junctional ectopic tachycardia and acute kidney injury after pediatric cardiac surgery: A meta‐analysis. (27th September 2018) - Li, Xin; Zhang, Chengxin; Dai, Di; Liu, Haiyuan; Ge, Shenglin
Abstract: Objective: We conducted a meta‐analysis to evaluate the effects of prophylactic perioperative dexmedetomidine administration on postoperative junctional ectopic tachycardia (JET) and acute kidney injury (AKI) in pediatric patients having undergone cardiac surgery. Design: This systematic review was registered with PROSPERO (CRD42017083880). Databases including PubMed, Cochrane Central Register of Controlled Trials, and Web of Science were searched for randomized controlled trials (RCTs) and observational cohort studies from its inception to March 2018. Two reviewers independently screened literature, extracted data, and assessed the quality of included studies using the Jadad scale and Newcastle‐Ottawa score. Meta‐analysis was then conducted by RevMan 5.3 and Stata 12.0 software. P value < .05 was considered significant. Results: A total of nine eligible studies (5 RCTs and 4 observational studies) comprising 1851 patients were selected for the final analysis. The results of meta‐analysis showed that dexmedetomidine significantly reduced the incidence of postoperative JET (OR =0.35, 95% CI: 0.22 to 0.53, P < .00001), but there was no significant difference between groups in AKI (OR =0.44, 95% CI: 0.19 to 1.04, P = .06) and all‐cause mortality (OR =0.87, 95% CI: 0.35 to 2.14, P = .77). Conclusions: The administration of perioperative dexmedetomidine effectively prevents JET in pediatric patients undergoing cardiac surgery but has no significant effect on postoperative renal function. However, the quality of evidence for these findings is low; thus, future larger scale randomized studies are needed to verify the real clinical effects of dexmedetomidine prophylaxis in pediatric patients.